EDUCATION OF THE IMPACT OF SMARTPHONE USE ON SPEAKING AND LANGUAGE ABILITIES IN EARLY CHILDHOOD IN KHADIJAH KINDERGARTEN 201, BANYUWANGI REGENCY: EDUCATION OF THE IMPACT OF SMARTPHONE USE ON SPEAKING AND LANGUAGE ABILITIES IN EARLY CHILDHOOD IN KHADIJAH KINDERGARTEN 201, BANYUWANGI REGENCY - nofitasari, intan (LPPM Universitas dr. Soebandi, 2024)
Abstract The use of smartphones in various fields means that smartphones are used by various groups, including children. In fact, quite a few parents introduce smartphones to their children under five years old with the excuse of